Investigating the Relationship Between Motivation and Self-regulated Learning Towards Physics Subject Among Foundation Students - A’bir Wardati binti Abd.Latif; Siti Aisyah Zawawi; Ku Siti Syahidah Ku Mohd Noh; Nor Fadzilah Arom Karoman; Haslinawati Mohd Mustapha; Nadiah Kamaruzaman (Universisti Teknologi MARA Press, 2024)
Indexed by MyCite